Penerapan Waterfall Pada Sistem Kasir UMKM Desa Pakisputih Berbasis Android - Mahardika, Fajar; Nurhadi, M. Ikhwan; Asri, Kuntari Wuri; Nurvianti, Desilia; Faza, Fariz (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
Technological developments go straight with the development of Micro, Small and Medium Enterprises, one of which is the sales or cashier system. This sales or cashier system is the answer to the problems that exist in one of the MSMEs in Pakisputih village. The results of observations and interviews with micro, small and medium business owners, the problem is that the transaction process is still manual using written notes, so it is very risky for notes to be lost or damaged, the profit calculation process is sometimes out of balance due to human error during the recapitulation process and there is no debt record so that when the reseller debt payment process is sometimes out of sync. The purpose of making this system is to assist the process of sales activities in micro, small and medium enterprises, help manage savings, and assist the process of recapitulating income statements. The stages of research here use the Waterfall method. This method helps in making and analyzing the cashier system that will be made. The results of this research are in the form of an Android-based Sales Cashier System for Micro, Small and Medium Enterprises that chooses multi-user access rights and is equipped with transaction features, savings management and income statements